Improve maximal aerobic speed in handball seniors through intermittent effort - Cazan, F.; Rizescu, C.; Georgescu, A. (Science, Movement & Health, 2013)
Working at high intensity intervals, the maximum aerobic speed aims central and peripheral qualities of maximum oxygen consumption. Through this experiment we want to improve its ability to repeat short explosive efforts and also to allow athlets more time to be quickly and strong more often. Material and methods: Experimental strategy implementation period was 8 weeks during July and August 2010. The research was conducted on HCM Constanta senior team participating in the National Handball League 2010 -2011 edition. The team is a group composed of 18 players, with a mean age of 26,94±3,78 years. Study took place in Sports Hall of Constanta, the team conducted its official matches, with a field approved by the Romanian Handball Federation and the track Farul Stadium in Constanta. We will include specific physical training program with a training schedule intermittent effort. We use such intermittent longer races more or less long, long intervals since the sequence of effort / rest 3-3 minutes, 2-2 minutes, then intermittent sprint 30 meters and passing through the more classical intermitent: 30"-30", 20"-20". These flights will be carried out at speeds close to maximum aerobic speed (VMA) using the 30-15 IFT (intermittent effort test) on intensity between 80 and 110% of flights will also be performed in line or commuting, or made way through periods of game activity effectively reduced for periods of 3 to 4 minutes. At the beginning and end of the training program, athletes were tested to determine VMA by 30-15 IFT. Results: After applying the new program designed by intermittent effort, we managed to improve maximal aerobic speed, men handball team HCM Constanta from17.21 to 18.83 km / h. Conclusions: After applying the training program with intermittent effort we managed to improve its ability to repeat short explosive efforts and also to allow athletes more time to be fast and powerful often.